ANALISIS PENERAPAN PROBLEM BASED LEARNING MELALUI PROYEK DIORAMA DALAM MENDORONG KETERLIBATAN PESERTA DIDIK - Mufihatun, Irma; Krisdiyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of the Problem Based Learning (PBL) model through a diorama project in encouraging student engagement in a Natural and Social Sciences (IPAS) lesson. The research was motivated by the demand of the Kurikulum Merdeka for student-centred learning that actively involves learners, whereas classroom practice still tends to be teacher-dominated. This study aims to describe the implementation of PBL through the diorama project and to analyse the forms of behavioural, emotional, and cognitive engagement that emerge among students. A qualitative descriptive approach with a case-study design was used, and data were collected through direct observation of guided teaching practice in a fourth-grade class of 20 students at SD Negeri Trangsan 01. The results show that PBL, combined with the